2000
DOI: 10.1086/302760
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Spectrum in the Δ7-Sterol Reductase Gene and Genotype-Phenotype Correlation in 84 Patients with Smith-Lemli-Opitz Syndrome

Abstract: Smith-Lemli-Opitz syndrome (SLOS), an autosomal recessive malformation syndrome, ranges in clinical severity from mild dysmorphism and moderate mental retardation to severe congenital malformation and intrauterine lethality. Mutations in the gene for Delta7-sterol reductase (DHCR7), which catalyzes the final step in cholesterol biosynthesis in the endoplasmic reticulum (ER), cause SLOS. We have determined, in 84 patients with clinically and biochemically characterized SLOS (detection rate 96%), the mutational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
221
0
3

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(237 citation statements)
references
References 29 publications
(40 reference statements)
13
221
0
3
Order By: Relevance
“…9 Recently the gene coding for DHCR7 has been cloned 14 and mutations in the gene were identified in all patients with biochemically confirmed SLOS. [15][16][17][18][19][20] The mutational spectrum in the DHCR7 gene from a large group of patients with SLOS has been determined and a genotype-phenotype correlation has been established. 18 Altogether over 40 DHCR7 mutations have been described in SLOS patients some of which were frequent.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently the gene coding for DHCR7 has been cloned 14 and mutations in the gene were identified in all patients with biochemically confirmed SLOS. [15][16][17][18][19][20] The mutational spectrum in the DHCR7 gene from a large group of patients with SLOS has been determined and a genotype-phenotype correlation has been established. 18 Altogether over 40 DHCR7 mutations have been described in SLOS patients some of which were frequent.…”
Section: Introductionmentioning
confidence: 99%
“…Although SLOS was initially classified clinically into two groups, SLO type I and SLO type II, based upon clinical criteria and severity, current observations suggest that these are but two ends of a continuous spectrum of severity. In previous investigations, we and others have shown that severity of SLOS disease correlates with plasma cholesterol levels, but that this does not account for all of the observed variations in severity [5,10]. Additionally, it is not uncommon to note dissimilar phenotypes in affected siblings, suggesting that factors other than mutations in DHCR7 affect phenotype.…”
Section: Introductionmentioning
confidence: 74%
“…Genotype-phenotype correlations show that a wide-spectrum of mutations in the DHCR7 gene can cause SLOS, but these mutations may account for only an estimated 50% of the severity of the disease [10,30]. Within a single family, the severity scores of two affected siblings can be different [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations